Preparation method and application of catalyst for array carbon nanotube with ultrahigh length-diameter ratio

By using a catalyst preparation method without layered compounds, a multi-compartment ring network structure is formed using organic complexing agents and cosolvents, the problems of multiple impurities and thick nickel-type tube diameters in the prior art are solved, and carbon nanotube preparation with high aspect ratio and thin tube diameters are achieved, reducing cost and process complexity.

CN119857538APending Publication Date: 2025-04-22WUXI NO 6 ELEMENT NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510099836.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, when preparing array carbon nanotubes, the process is complicated due to the large amount of layered support impurities in the catalyst, the nickel-type tube diameter is thicker, and there is a lack of a preparation method for a high aspect ratio carbon nanotube.

Method used

Using a method without the need for a layered compound as a support, a catalyst precursor with a highly ordered multi-ring network structure is formed by stirring and aging of solutions A and B, and the target catalyst is obtained by high temperature calcination, and an array carbon nanotube with ultra-high aspect ratio is prepared.

Benefits of technology

It is possible to prepare efficient catalysts without layered compounds, reduce the production cost and process complexity, and obtain carbon nanotubes with high aspect ratio (9400-53000) and thin tube diameters (3-9nm, average 5.5nm).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857538A_ABST
    Figure CN119857538A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a catalyst for an array carbon nanotube with an ultrahigh length-diameter ratio, which can be used for preparing the catalyst without using a layered compound as a carrier and can be used for manufacturing the carbon nanotube with a high length-diameter ratio at a lower cost. The added organic complex and cosolvent contain a large amount of carboxyl, carbonyl, amino and other groups, iron and nickel ions in active metal and the groups are self-assembled to form a highly ordered multi-ring network structure, and the multi-ring network structure is a metal organic framework compound MOFs. A flaky catalyst is obtained after drying and high-temperature roasting, high-melting-point auxiliary metal (Mo, W and V) and active metal in the catalyst form a co-solution, distribution of the active metal on a carrier is improved, the agglomeration phenomenon of active metal nickel-iron particles is reduced, and it is ensured that the particle size of metal particles in the catalyst produced in the invention is small. Meanwhile, the invention further discloses a preparation method of the array carbon nanotube with the ultrahigh length-diameter ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon nanotube preparation, in particular to a method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes and its application. Background Art

[0002] Carbon nanotubes (CNTs) have excellent optical, thermal, acoustic, mechanical, electrical and chemical properties due to their special one-dimensional tubular structure, and are widely used in catalyst carriers, lithium-ion batteries, sodium-ion batteries, nanodevices and composite material reinforcement. The main methods for preparing carbon nanotubes are arc method, laser evaporation method and chemical vapor deposition method, among which chemical vapor deposition method is currently the most commonly used method for preparing carbon nanotubes.

[0003] Carbon nanotubes can be divided into entangled CNTs and arrayed CNTs according to their aggregation state. Among them, arrayed CNTs refer to CNTs that are orderly oriented and arranged in parallel under certain conditions. The catalysts currently used to prepare arrayed carbon nanotubes are mainly based on layered compounds (such as vermiculite, mica, montmorillonite, etc.) as carriers, and the active substances iron, cobalt and nickel are loaded in them; the main disadvantage of this method is that the layered compounds themselves contain a large amount of impurities, which need to be removed by oxidation or pickling, and are prone to produce environmental problems such as waste acid and wastewater.

[0004] Carbon nanotubes have a wide range of applications in composite reinforcement (especially natural rubber) due to their high aspect ratio. However, there are few or even almost no carbon nanotubes with a high aspect ratio of more than 9000 on the market. For example, patent CN 114887626 A "A method for preparing a carbon nanotube catalyst with a high specific surface area and a high aspect ratio" discloses a hydrothermal method for preparing a carbon nanotube catalyst using iron and cobalt as active substances, Mo as an auxiliary agent, magnesium and aluminum as carriers, and urea as a precipitant. The patent mentions that the diameter of the obtained carbon nanotube is 5-8nm and the length is 25-30μm. It is calculated that the aspect ratio of the carbon nanotube is between 3125 and 6000. In addition, the catalyst cracking rate of the carbon source is not mentioned. Patent CN 108046239 A "A carbon nanotube with a high aspect ratio and a method for preparing it" discloses a carbon nanotube with a high aspect ratio obtained by high-temperature roasting of a mixture of iron, cobalt, nickel and asphalt. The diameter of the carbon nanotubes prepared by this patent is less than 70nm, the tube length is greater than 300μm, and the calculated aspect ratio of this carbon nanotube is about 4300. Patent CN114455572 B "A method for preparing high aspect ratio carbon nanotubes using waste liquid oil as a carbon source" discloses a method of mixing waste liquid oil with a catalyst (composed of ferrocene and nickelocene) and a growth promoter thiophene, and then spraying the mixture with protective gas into a high-temperature reactor through a sprayer to obtain high aspect ratio carbon nanotubes; the aspect ratio of the carbon nanotubes obtained by this patent is between 4000 and 5800.

[0005] At present, carbon nanotubes prepared by catalysts with nickel as active material are generally thick tubes (tube diameter is about 30-100nm). For example, patent CN 1186251C "A catalyst for preparing carbon nanotubes and its preparation method" discloses a catalyst precursor with nickel, magnesium and copper oxides, which is reduced by hydrogen to obtain the desired catalyst, and the carbon source is cracked at high temperature to obtain carbon nanotubes with a diameter of 20-50nm. Patent 115532276 A "Preparation and application of a nickel-based carbon nanotube catalyst" discloses a carbon nanotube catalyst obtained by calcining nickel nitrate, aluminum nitrate, ammonium molybdate, chromium nitrate and citric acid, which cracks propane to obtain carbon nanotubes with a diameter of about 30-60nm. Summary of the invention

[0006] In order to solve the problems in the prior art of preparing array-type carbon nanotubes, such as the complicated process due to the large number of impurities in the catalyst layered carrier, the thick diameter of the nickel-based tube, and the lack of a preparation method for high aspect ratio carbon nanotubes, the present invention provides a method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes, which can prepare catalysts without using layered compounds as carriers, and manufacture high aspect ratio carbon nanotubes at a lower cost. At the same time, the application also discloses a method for preparing ultra-high aspect ratio array carbon nanotubes.

[0007] The technical solution of the present invention is as follows: a method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes, characterized in that it comprises the following steps: S1: Weigh an appropriate amount of soluble metal salt and organic complexing agent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution A; The soluble metal salts include: active material soluble metal salts and carrier soluble metal salts; The organic complexing agent mainly includes: oxalic acid, urea and amino acid substances; S2: Weigh an appropriate amount of auxiliary metal salt and co-solvent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution B; The co-solvent mainly includes: at least one or any combination of ammonium citrate, citric acid, ammonium carbonate and ammonium bicarbonate; The auxiliary metal salt includes: at least one or any combination of ammonium molybdate, ammonium metatungstate and ammonium metavanadate; S3: Continue stirring solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, marked as solution C; S4: After the solution C is allowed to stand for a period of time, it is placed in an oven to dry until there is no obvious liquid flow, thereby obtaining a catalyst precursor; S5: After calcining the catalyst precursor at high temperature for a period of time, cooling it to room temperature, taking it out and sealing it for storage to obtain the target catalyst.

[0008] It is further characterized by: In step S4, the aging time of solution C is set to be greater than 10 hours, and the drying temperature is 70-90°C; In step S5, the catalyst precursor is calcined at a temperature of 400-700° C. for a time of 2-8 hours; The organic complexing agent comprises: at least one or any combination of oxalic acid, urea, glycine, L-alanine, β-alanine, L-valine, L-leucine, L-proline, L-threonine, L-phenylalanine, L-arginine and L-aspartic acid; The active material soluble metal salts include: soluble nickel salts and soluble iron salts; The carrier soluble metal salts include: soluble copper salts, soluble zinc salts, soluble magnesium salts, soluble manganese salts and soluble aluminum salts; the configuration must include soluble aluminum salts, and at least one or any combination of other carrier soluble metal salts; The soluble nickel salt is at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; The soluble copper salt is at least one or any combination of copper nitrate, copper acetate, copper chloride and copper sulfate; The soluble iron salt is at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; The soluble zinc salt is at least one or any combination of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; The soluble magnesium salt is at least one or any combination of magnesium nitrate, magnesium chloride, magnesium acetate and magnesium sulfate; The soluble manganese salt is at least one or any combination of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate; The soluble aluminum salt is at least one or any combination of aluminum nitrate, aluminum chloride, aluminum acetate and aluminum sulfate; In the soluble metal salt, according to the catalyst components obtained after the final preparation, the mass fraction of metal Ni in the final catalyst is 10-25%, and the molar ratio of Fe to Ni included in the soluble metal salt is between 0.5 and 2. The carrier metal includes: Al, Cu, Zn, Mn and Mg, wherein the molar ratio of the sum of Cu, Zn, Mn and Mg to the active metal Ni is between 0.05 and 1.0; The mass ratio of the cosolvent to the auxiliary metal salt is between 0.8-1.5; the mass ratio of the auxiliary metal salt to the mass ratio of the active substance metal salt is 0.01-0.20; The molar ratio of the organic complexing agent to the metal salt is between 0.3 and 0.9; In step S1, 10.00 g of nickel nitrate hexahydrate, 10.42 g of iron nitrate nonahydrate, 3.15 g of zinc nitrate, 34.43 g of aluminum nitrate nonahydrate and 8.40 g of L-alanine were weighed and placed in a 200 mL beaker filled with 50 mL of deionized water, and stirred continuously until dissolved into a transparent solution, which was marked as active metal solution A; In step S2, 1.20 g of ammonium metatungstate and 1.20 g of ammonium carbonate were weighed and dissolved in 20 ml of deionized water to form solution B; In step S3, solution A is continuously stirred, solution B is added to solution A, and stirring is continued until the solution becomes clear and transparent, which is marked as solution C; In step S4, solution C is allowed to stand for 11 hours and then placed in an oven at 80° C. to dry until there is no obvious liquid flow, thereby obtaining a catalyst precursor; In step S5, the catalyst precursor is calcined at 600°C for 3 hours, cooled to room temperature, taken out and sealed for storage to obtain the target catalyst.

[0009] A method for preparing an ultra-high aspect ratio array carbon nanotube, characterized in that it comprises the following steps: a1: Weigh the catalyst and place it in a boat for later use; a2: Load the boat containing the catalyst into the fixed bed reactor and seal it; a3: N2 is introduced, and then the fixed bed reactor is heated to 650-700°C; a4: After the temperature in the reactor is stabilized, cracking gas propane is introduced to carry out cracking reaction; a5: After the cracking reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.

[0010] It is further characterized by: In step a1, 1.25 of the catalyst was weighed, divided into 5 equal portions, and placed in 5 material boats for later use; In step a3, 122 L / h N2 was introduced, and then the fixed bed reactor was heated to 690°C.

[0011] In step a4, after the temperature in the reactor is stabilized, 194.84 L / h propane is introduced into the reactor to carry out a cracking reaction, and the cracking reaction time is 0.5-2 h.

[0012] The present application provides a method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes, wherein the organic complex and cosolvent added contain a large number of carboxyl, carbonyl, amino and other groups, and the iron and nickel ions in the active metal form a highly ordered multi-ring network structure with these groups through self-assembly, and the multi-ring network structure is a metal organic framework compound MOFs, which is dried and calcined at high temperature to obtain a flaky catalyst, that is, based on the technical solution of the present application, a layered catalyst can be prepared without the need to add additional layered compounds as templates. In the technical solution of the present application, high melting point auxiliary metals (Mo, W and V) are used to form a co-solvent with the active metal in the catalyst, which is conducive to reducing the particle size of the catalyst, improving the distribution of the active metal on the carrier, reducing the agglomeration of the active metal nickel-iron particles, ensuring that the metal particle size in the catalyst produced in the present application is small, and thus ensuring that the diameter of the carbon nanotubes generated by the cracking of the carbon source by the catalyst in the present application is thinner. In the present application, carbon nanotubes are prepared based on propane as a carbon source. From the perspective of the price of the carbon source itself, the carbon content, and the energy required for cracking, propane is a carbon source option that can achieve a balance between cost and yield. In the present application, by aging solution C, during the aging process of solution C, a series of self-assembly processes occur at room temperature for substances such as complexing agents, metal salts, additives, and co-solvents, resulting in changes in the final catalyst structure, thereby increasing the effective generation rate of layered catalysts, increasing the catalyst cracking rate of propane, and thereby increasing the carbon nanotube rate. Therefore, based on the technical solution of the present application, catalysts can be prepared without layered compounds as carriers, and carbon nanotubes with a high aspect ratio can be manufactured at a relatively low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The whole and local TEM electron microscope images of the catalyst prepared in Example 1; Figure 2 The whole and local SEM electron microscope pictures of the catalyst prepared in Example 1; Figure 3 The whole and local TEM electron microscope images of carbon nanotubes (average tube diameter of 5.5 nm) obtained from propane cracking by the catalyst in Example 1; Figure 4 The overall and local SEM electron microscope images of carbon nanotubes (average tube diameter of 5.5 nm) obtained from propane cracking by the catalyst in Example 1; Figure 5 This is a diagram showing the diameter distribution of carbon nanotubes obtained by cracking propane with the catalyst in Example 1. DETAILED DESCRIPTION

[0014] The present invention includes a method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes, characterized in that it includes the following steps: S1: Weigh an appropriate amount of soluble metal salt and organic complexing agent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution A; The soluble metal salts include: active material soluble metal salts and carrier soluble metal salts.

[0015] In this embodiment, nickel and iron are used as active materials, and magnesium, aluminum, manganese, zinc and copper are used as carrier materials.

[0016] The soluble metal salts of the active material include: soluble nickel salts and soluble iron salts; the soluble metal salts of the carrier include: soluble copper salts, soluble zinc salts, soluble magnesium salts, soluble manganese salts and soluble aluminum salts, which must include soluble aluminum salts, and at least one or any combination of other soluble metal salts of the carrier; The soluble nickel salt is at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; The soluble copper salt is at least one or any combination of copper nitrate, copper acetate, copper chloride and copper sulfate; The soluble iron salt is at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; The soluble zinc salt is at least one or any combination of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; The soluble magnesium salt is at least one or any combination of magnesium nitrate, magnesium chloride, magnesium acetate and magnesium sulfate; The soluble manganese salt is at least one or any combination of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate; The soluble aluminum salt is at least one or any combination of aluminum nitrate, aluminum chloride, aluminum acetate and aluminum sulfate; The organic complexing agent mainly includes at least one or any combination of amino acid substances such as oxalic acid, urea, glycine, L-alanine, β-alanine, L-valine, L-leucine, L-proline, L-threonine, L-phenylalanine, L-arginine and L-aspartic acid.

[0017] In step S1, in the soluble metal salt, according to the catalyst components obtained after the final preparation, the mass fraction of metal Ni in the final catalyst is 10-25%, and the molar ratio of Fe to Ni included in the soluble metal salt is between 0.5 and 2. The carrier metals include: Al, Cu, Zn, Mn and Mg, wherein the molar ratio of the sum of Cu, Zn, Mn and Mg to the active metal Ni is between 0.05 and 1.0; the addition of the carrier metals Cu, Zn, Mn and Mg can significantly improve the acid sites on the surface of the carrier Al2O3, change the binding force between the active metal and the carrier, increase the active sites of the catalyst for cracking the carbon source as a whole, and further increase the generation rate of carbon nanotubes. When the molar ratio of the sum of the carrier metals Cu, Zn, Mn and Mg to the active metal Ni is lower than 0.05, the generation rate of carbon nanotubes cannot be significantly increased due to the small amount of addition; and when the molar ratio of the carrier metal to the active metal Ni is higher than 1.0, the content of the sum of the carrier metals Cu, Zn, Mn and Mg is high, which destroys the dominant position of the carrier Al2O3 content, resulting in a decrease in the generation rate of carbon nanotubes.

[0018] The molar ratio of the organic complexing agent to the metal salt is between 0.3 and 0.9; the organic complex and the cosolvent added when preparing the catalyst contain a large number of carboxyl, carbonyl, amino and other groups, and the metal ions in the present invention and these groups form a highly ordered multi-ring network structure (i.e., metal organic framework compound, MOFs for short) through self-assembly. When the molar ratio of the added organic complexing agent to the metal salt is lower than 0.3, the morphology of the prepared catalyst changes fundamentally, and it is no longer a thin sheet structure, but irregular particles. The corresponding carbon nanotubes obtained after cracking propane are no longer array tubes, but winding tubes; and when the ratio is greater than 0.9, due to the presence of a large amount of organic complexing agent, a large amount of combustion occurs during the roasting process, resulting in partial sintering of the catalyst active material, and the active metal particles become larger, which reduces the carbon nanotube generation rate while increasing the diameter of the carbon nanotube.

[0019] S2: Weigh an appropriate amount of auxiliary metal salt and auxiliary solvent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution B.

[0020] The co-solvent mainly includes: at least one or any combination of ammonium citrate, citric acid, ammonium carbonate and ammonium bicarbonate.

[0021] The auxiliary metal salt includes: at least one or any combination of ammonium molybdate, ammonium metatungstate and ammonium metavanadate; the auxiliary metal salt mainly plays the role of assisting the activation of the catalyst in the catalyst cracking propane reaction, and generally the melting point of such auxiliary agents is relatively high, above 2000°C; it can form a co-solvent with the active metal in the catalyst, which is conducive to reducing the particle size of the catalyst, ensuring that the diameter of the carbon nanotubes finally generated is small and uniform, and at the same time, it can also improve the distribution of the active metal on the carrier, reduce the agglomeration of the active metal nickel-iron particles, ensure that the active metal is evenly distributed on the carrier, and finally improve the yield of the carbon nanotubes. At present, the carbon nanotubes prepared by the catalyst with nickel as the active substance are generally thick tubes (diameter of about 30-100nm), and the nickel-based carbon nanotubes prepared in this application are thinner, with a diameter range of 3-9nm, of which more than 80% are concentrated in 3-7nm, and the average diameter is 5.5nm.

[0022] The mass ratio of the co-solvent to the auxiliary metal salt is between 0.8 and 1.5.

[0023] The ratio of the total mass of the auxiliary metal salt to the total mass of the active substance metal salt is: 0.01-0.20; when the ratio of the total mass of the auxiliary metal to the total mass of the active substance metal salt is lower than 0.01, the auxiliary metal cannot play a role in assisting the activation of the catalyst due to its low content; when the ratio of the total mass of the auxiliary metal to the total mass of the active substance metal salt is higher than 0.20, the auxiliary metal competes with the active metal for the reactive sites due to its high content, and since the auxiliary metal itself has no activity or very low activity, the active sites of the catalyst are reduced, and the ability to crack carbon sources is reduced.

[0024] S3: Continue stirring solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, marked as solution C.

[0025] S4: After the solution C is allowed to stand for a period of time, it is placed in an oven to dry until there is no obvious liquid flow, thereby obtaining a catalyst precursor.

[0026] The aging time of solution C is set to be greater than 10 hours. In this embodiment, the aging time of solution C is set to 10 hours to 20 hours. After the aging is completed, the solution C without obvious liquid flow is placed in a 70-90° C. oven to dry to obtain a catalyst precursor.

[0027] During the aging process of solution C, the complexing agent, metal salt, additive and co-solvent reacted a series of self-assembly processes at room temperature, resulting in changes in the final catalyst structure. When the aging time exceeds 10 hours, the prepared catalyst can increase the cracking rate of propane, which is 13% higher than that of the catalyst that has not been aged.

[0028] The aged solution C is then dried in an oven until there is no obvious liquid flow. The catalyst prepared in this state has a propane cracking rate that is 20%-30% higher than that of the undried catalyst.

[0029] S5: After calcining the catalyst precursor at high temperature for a period of time, the catalyst precursor is cooled to room temperature and then taken out and sealed for storage to obtain the target catalyst.

[0030] In this embodiment, the catalyst precursor is calcined at 400-700° C. for 2-8 hours, and after cooling to room temperature, taken out and sealed for storage to obtain the target catalyst.

[0031] The organic complex and cosolvent added during the preparation of the catalyst contain a large number of carboxyl, carbonyl, amino and other groups. The metal ions in the present invention and these groups self-assemble to form a highly ordered multi-ring network structure (i.e., metal organic framework compounds, MOFs for short). Therefore, the present application can prepare a layered catalyst without the need to add additional layered compounds as templates, effectively reducing the preparation process and cost of the catalyst. At the same time, because the auxiliary metal salts include high melting point auxiliary metals such as ammonium molybdate, ammonium metatungstate and ammonium metavanadate, they form a co-solvent with the active metal in the catalyst, effectively reducing the particle size of the catalyst, ensuring that the technical solution of the present application can prepare a catalyst for preparing ultra-high aspect ratio array carbon nanotubes using nickel iron as the active substance.

[0032] Referring to the drawings of the specification Figure 1 and Figure 2 , indicating that the catalyst prepared in this application is a flake structure with a width ranging from several hundred nanometers to several microns. From the locally enlarged picture, it can be seen that the flake is assembled from a large number of small hexagonal metal oxide nanosheets (10-30nm). Figure 3 This is an image of carbon nanotubes produced based on the technical solution of the present application, indicating that the carbon nanotubes prepared by the nickel-iron catalyst of the present invention have thinner diameters, ranging from 3 to 9 nm, of which more than 80% are concentrated in 3 to 7 nm, and the average diameter is 5.5 nm.

[0033] Methane, ethylene, propylene, acetylene and other hydrocarbon compounds are commonly used carbon sources. Currently, the most commonly used carbon source is propylene. Propylene is widely used due to its high energy and easy cracking characteristics, but the current cost of commercially available propylene is relatively high. In addition, some manufacturers use methane as a carbon source to prepare carbon nanotubes. Methane is a low-cost gas source and the most stable substance among alkane hydrocarbons. At the same time, the energy required for its cracking is relatively high, and its carbon content itself is the lowest among alkanes, at 75%. Considering the price, carbon content, and energy required for cracking of the carbon source itself, this application uses propane as the carbon source.

[0034] The present application also includes a method for preparing an ultra-high aspect ratio array carbon nanotube, which includes the following steps.

[0035] a1: Weigh the catalyst produced by the above method and place it in a boat for later use; In this embodiment, 1.25 catalyst (divided into 5 equal portions and placed in 5 material boats) was weighed for use; a2: Loading the boat containing the catalyst into the fixed bed reactor and sealing it; a3: 122 L / h N2 was introduced, and then the fixed bed reactor was heated to 650-700°C; a4: After the temperature in the reactor is stabilized, 194.84 L / h propane is introduced to carry out cracking reaction. The cracking reaction time is 0.5-2 h; a5: After the cracking reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.

[0036] In this application, the carbon nanotube rate is calculated as follows: Ratio = (mass of carbon nanotubes / mass of catalyst) -1.

[0037] In the present application, the aspect ratio is the ratio between the length and the diameter of the carbon nanotube.

[0038] The catalyst of the present application is a layered structure, so the carbon nanotubes grown based on the catalyst are vertical array carbon nanotubes. Figure 4 It shows that the growth mode of the carbon nanotubes prepared by the catalyst of the present invention is vertical growth, and the tube length is between 85-160 μm. Figure 5 This indicates that more than 80% of the carbon nanotubes prepared in Example 1 have a diameter within 7 nm.

[0039] The following is an explanation of the catalyst preparation and carbon nanotube preparation process based on examples.

[0040] The catalyst preparation process of Example 1 is as follows: S1: Weigh 10.00 g nickel nitrate hexahydrate, 10.42 g iron nitrate nonahydrate, 3.15 g zinc nitrate, 34.43 g aluminum nitrate nonahydrate and 8.4 g L-alanine into a 200 mL beaker filled with 50 mL deionized water, and continue stirring until dissolved into a transparent solution, marked as active metal solution A; S2: Weigh 1.20 g of ammonium metatungstate and 1.20 g of ammonium carbonate and dissolve them in 20 ml of deionized water to form solution B; S3: Continue stirring solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, marked as solution C; S4: After aging solution C for 11 h, place it in an oven at 80°C to dry until there is no obvious liquid flow; S5: calcining the catalyst precursor at 600° C. for 3 h, cooling it to room temperature, taking it out and sealing it for storage to obtain the target catalyst.

[0041] The catalyst cracking propane process of Example 1 is as follows: Weigh 1.25 of catalyst (divided into 5 equal portions and placed in 5 material boats) for use.

[0042] The catalyst boat was loaded into the fixed bed reactor and sealed. 122L / h N2 was introduced, and then the fixed bed reactor was heated to 690°C. After the temperature in the reactor stabilized, cracking gas (194.84L / h propane) was introduced. The cracking reaction time was 0.5-2h. After the reaction was completed, heating was stopped, and N2 was introduced to replace the cracking gas until the temperature dropped to room temperature to obtain array CNTs.

[0043] Example 2 is prepared in the same manner as Example 1, except that the carrier in the catalyst preparation is replaced by manganese nitrate instead of zinc nitrate.

[0044] Example 3 is prepared in the same manner as Example 1, except that the carrier in the catalyst preparation is replaced by copper nitrate instead of zinc nitrate.

[0045] Example 4 is prepared in the same manner as Example 1, except that the auxiliary metal salt in the catalyst preparation is replaced by ammonium metatungstate to ammonium metavanadate.

[0046] Example 5 The preparation method is the same as that of Example 1, except that the auxiliary metal salt in the catalyst preparation is replaced by ammonium metatungstate to ammonium molybdate.

[0047] Example 6 is prepared in the same manner as Example 1, except that the co-solvent in the catalyst preparation is replaced by ammonium carbonate with ammonium citrate.

[0048] Example 7 The preparation method is the same as that of Example 1, except that the co-solvent in the catalyst preparation is replaced by citric acid instead of ammonium carbonate.

[0049] Example 8 The preparation method is the same as that of Example 1, except that the co-solvent in the catalyst preparation is replaced by ammonium carbonate to ammonium bicarbonate.

[0050] Example 9 The preparation method is the same as that of Example 1, except that the organic complexing agent in the catalyst preparation is replaced by glycine instead of L-alanine.

[0051] Example 10 is prepared in the same manner as Example 1, except that the masses of ferric nitrate nonahydrate, zinc nitrate and aluminum nitrate nonahydrate in the catalyst preparation are changed to 17.37 g, 1.26 g and 25.40 g, respectively.

[0052] Comparative Example 1 was prepared in the same manner as in Example 1, except that solution C was not aged during catalyst preparation but was directly dried.

[0053] Comparative Example 2 was prepared in the same manner as in Example 1, except that during the catalyst preparation process, solution C was not dried but directly calcined.

[0054] Comparative Example 3 was prepared in the same manner as Example 1, except that the masses of ferric nitrate nonahydrate, zinc nitrate and aluminum nitrate nonahydrate in the catalyst preparation were changed to 1.39 g, 7.57 g and 142.39 g, respectively.

[0055] Comparative Example 4 was prepared in the same manner as Example 1, except that the masses of ferric nitrate nonahydrate, zinc nitrate and aluminum nitrate nonahydrate in the catalyst preparation were changed to 5.56 g, 6.94 g and 10.85 g, respectively.

[0056] Comparative Example 5 was prepared in the same manner as Example 1, except that the amount of the organic complexing agent in the catalyst preparation was changed, and the amount of L-alanine was reduced to 1 / 4.

[0057] The preparation results of the above examples and comparative examples are shown in Table 1.

[0058] Table 1 Summary of corresponding carbon tube data in the examples of preparing carbon tubes

[0059] Based on the data in Table 1, it can be seen that the ratio of Example 1 is the best ratio, and the aspect ratio of the carbon nanotubes produced therefrom is the best and the carbon nanotube ratio is the largest. Figure 1~Figure 5 The data are all collected based on the catalyst and carbon nanotubes produced in Example 1. Figure 5 This is a diagram showing the diameter distribution of carbon nanotubes obtained by cracking propane with the catalyst in Example 1.

[0060] Comparative Examples 1 and 2 are treatments of Solution C, omitting the aging step and the drying step, respectively. It can be seen that the final carbon tube ratio is relatively low.

[0061] Comparative Examples 3-5 are data outside the above formulation range. The carbon nanotubes obtained with the formulations outside the formulation range of the present application have larger diameters and shorter tube lengths, and the corresponding aspect ratios are lower.

[0062] The carrier, auxiliary metal salt, auxiliary solvent, and organic complexing agent used in the above embodiments can all be used to generate catalysts based on this method, and carbon nanotubes can be produced based on the catalyst using propane as a carbon source.

[0063] When the present method is used for production, any existing commercial raw materials that meet the requirements can be used to produce catalysts and carbon nanotubes. The sources of the raw materials in this example are shown in Table 2.

[0064] Table 2 Raw material examples

[0065] After using the technical solution of the present invention, there is no need for layered compounds as carriers, and iron and nickel are used as active substances to prepare ultra-high aspect ratio array carbon nanotube catalysts in one step through the sol-gel method, and propane is used as a carbon source for catalytic cracking to prepare array CNTs. The array CNTs prepared by this method have moderate carbon source cost, high carbon yield (> 90), good dispersibility, good tube diameter uniformity (tube diameter range is 3-9nm, of which more than 80% are concentrated in 3-7nm, and the average tube diameter is 5.5nm), array tube length is between 85-160μm, aspect ratio is between 9400-53000, and specific surface area is low (220-270m 2 / g), moderate tap density (0.02-0.05g / cm 3 ), good conductivity (powder resistivity is between 8-12mΩ·cm).

Claims

1. A method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes, characterized in that: It includes the following steps: S1: Weigh an appropriate amount of soluble metal salt and organic complexing agent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution A; The soluble metal salts include: active material soluble metal salts and carrier soluble metal salts; The organic complexing agent mainly includes: oxalic acid, urea and amino acid substances; S2: Weigh an appropriate amount of auxiliary metal salt and co-solvent and place them in deionized water, and continue stirring until the solution is clear and transparent to form solution B; The co-solvent mainly includes: at least one or any combination of ammonium citrate, citric acid, ammonium carbonate and ammonium bicarbonate; The auxiliary metal salt includes: at least one or any combination of ammonium molybdate, ammonium metatungstate and ammonium metavanadate; S3: Continue stirring solution A, add solution B into solution A, and continue stirring until the solution is clear and transparent, marked as solution C; S4: After the solution C is allowed to stand for a period of time, it is placed in an oven to dry until there is no obvious liquid flow, thereby obtaining a catalyst precursor; S5: After calcining the catalyst precursor at high temperature for a period of time, cooling it to room temperature, taking it out and sealing it for storage to obtain the target catalyst.

2. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 1, characterized in that: In step S4, the aging time of solution C is set to be greater than 10 hours, and the drying temperature is 70-90°C.

3. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 1, characterized in that: In step S5, the catalyst precursor is calcined at a temperature of 400-700° C. for a time of 2-8 hours.

4. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 1, characterized in that: The organic complexing agent comprises at least one or any combination of oxalic acid, urea, glycine, L-alanine, β-alanine, L-valine, L-leucine, L-proline, L-threonine, L-phenylalanine, L-arginine and L-aspartic acid.

5. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 1, characterized in that: The active material soluble metal salts include: soluble nickel salts and soluble iron salts; The carrier soluble metal salts include: soluble copper salts, soluble zinc salts, soluble magnesium salts, soluble manganese salts and soluble aluminum salts; the configuration must include soluble aluminum salts, and at least one or any combination of other carrier soluble metal salts.

6. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 5, characterized in that: The soluble nickel salt is at least one or any combination of nickel nitrate, nickel acetate, nickel chloride and nickel sulfate; The soluble copper salt is at least one or any combination of copper nitrate, copper acetate, copper chloride and copper sulfate; The soluble iron salt is at least one or any combination of ferric nitrate, ferric acetate, ferric chloride and ferric sulfate; The soluble zinc salt is at least one or any combination of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; The soluble magnesium salt is at least one or any combination of magnesium nitrate, magnesium chloride, magnesium acetate and magnesium sulfate; The soluble manganese salt is at least one or any combination of manganese nitrate, manganese chloride, manganese acetate and manganese sulfate; The soluble aluminum salt is at least one or any combination of aluminum nitrate, aluminum chloride, aluminum acetate and aluminum sulfate.

7. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 5, characterized in that: In the soluble metal salt, according to the catalyst components obtained after the final preparation, the mass fraction of metal Ni in the final catalyst is 10-25%, and the molar ratio of Fe to Ni included in the soluble metal salt is between 0.5 and 2. The carrier metal includes: Al, Cu, Zn, Mn and Mg, wherein the molar ratio of the sum of Cu, Zn, Mn and Mg to the active metal Ni is between 0.05 and 1.0; The mass ratio of the cosolvent to the auxiliary metal salt is between 0.8-1.5; the mass ratio of the auxiliary metal salt to the mass ratio of the active substance metal salt is 0.01-0.20; The molar ratio of the organic complexing agent to the metal salt is between 0.3 and 0.

9.

8. The method for preparing a catalyst for ultra-high aspect ratio array carbon nanotubes according to claim 1, characterized in that: In step S1, 10.00 g of nickel nitrate hexahydrate, 10.42 g of iron nitrate nonahydrate, 3.15 g of zinc nitrate, 34.43 g of aluminum nitrate nonahydrate and 8.40 g of L-alanine were weighed and placed in a 200 mL beaker filled with 50 mL of deionized water, and stirred continuously until dissolved into a transparent solution, which was marked as active metal solution A; In step S2, 1.20 g of ammonium metatungstate and 1.20 g of ammonium carbonate were weighed and dissolved in 20 ml of deionized water to form solution B; In step S3, solution A is continuously stirred, solution B is added to solution A, and stirring is continued until the solution becomes clear and transparent, which is marked as solution C; In step S4, solution C is allowed to stand for 11 hours and then placed in an oven at 80° C. to dry until there is no obvious liquid flow, thereby obtaining a catalyst precursor; In step S5, the catalyst precursor is calcined at 600° C. for 3 h, cooled to room temperature, taken out and sealed for storage to obtain the target catalyst.

9. A method for preparing an ultra-high aspect ratio array carbon nanotube, characterized in that: It includes the following steps: a1: Weigh the catalyst and place it in a boat for later use; a2: Load the boat containing the catalyst into the fixed bed reactor and seal it; a3: N2 is introduced, and then the fixed bed reactor is heated to 650-700°C; a4: After the temperature in the reactor is stabilized, cracking gas propane is introduced to carry out cracking reaction; a5: After the cracking reaction is completed, heating is stopped and N2 is introduced to replace the cracking gas until the temperature drops to room temperature to obtain array CNTs.

10. The method for preparing an ultra-high aspect ratio array carbon nanotube according to claim 9, characterized in that: In step a1, 1.25 of the catalyst was weighed, divided into 5 equal portions, and placed in 5 material boats for later use; In step a3, 122 L / h N2 was introduced, and then the fixed bed reactor was heated to 690°C; In step a4, after the temperature in the reactor is stabilized, 194.84 L / h propane is introduced into the reactor to carry out a cracking reaction, and the cracking reaction time is 0.5-2 h.

Citation Information

Patent Citations

  • High-aspect-ratio carbon nano-tubes and preparation method thereof

    CN108046239A

  • A method for preparing high aspect ratio carbon nanotubes using waste liquid oil as carbon source

    CN114455572B

  • Preparation and application of nickel-based carbon nanotube catalyst

    CN115532276A